A FIRST REPORT ON THE ROLE OF TRACE ELEMENT PEDOGEOCHEMISTRY IN DIAMOND EXPLORATION- AN EXAMPLE FROM LATTAVARAM KIMBERLITE CLUSTER, SOUTHERN INDIA - Pothuri, Rameshchandra Phani (Geochimica Brasiliensis, 2018)
Trends in a concentration of selected trace elements in residual soils on four known diamondiferous kimberlite pipes (3, 4, 8 and 9) occurring at Lattavaram within the Wajrakarur Kimberlite Field (WKF) is attempted for the first time. The pipes 3 and 4 are exposed whereas the 8 and 9 are concealed under calcrete and colluvium. For this purpose, elements like Cr, Co, La, Nb, Ni, Mg, Sr and Zr are used to understand their concentrations in the kimberlitic soils in comparison with background granitic soils. It is observed that the soils on kimberlite pipes show conspicuous enrichment of elements such as Cr, Co, Nb, Ni, Mg and Sr when compared to soils in the country rock granitoid. However, no much variation in the elements La and Zr patterns between the kimberlitic and background soils is noticed. The high pulse in trace elements in kimberlitic soils is attributed to the presence of primary kimberlitic minerals in the soil. This particular aspect of pedogeochemistry is envisaged to be useful as an exploration tool in search of kimberlites in cratonic parts of southern India. An enrichment of Nb content upto 45 ppm in residual soils may be considered as anomalous in the craonic parts of Indian subcontinent, which needs to be confirmed and taken forward in conjunction with high-resolution geological mapping, geophysics and eventual drilling.